Agglomeration and endogenous absorptive capacities: hotelling revisited - Caroline Hussler; André Lorentz; Patrick Rondé (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper proposes a theoretical model of spatial duopoly, where the location, on the one hand, and the absorptive capacity of rms as function of their internal R&D investment, on the other hand, endogenously determine the maximum level of knowledge spillovers rms might absorb. Our goal is to test whether this new modelling of spillovers a ects the traditional outcomes in terms of rms location choices . We solve a three-stage game, where rms choose their geo- graphical location, prior to their level of internal R&D expenditures, and nally compete in prices. We found that, at the optimum, rms choose the same level of internal R&D and set the same price, inde- pendently of their location. Moreover, rms locate symmetrically and tends to agglomerate in the center of the market as the transportation costs increase, knowledge spillovers being in that case maximum.
Keywords: O33; R12; L13; 330; spatial agglomeration; endogenous spillovers; absorptive capacity; non-cooperative game; Agglomerationseffekt; Standorttheorie; Industrielle Forschung; Wissenstransfer; Hotelling Modell; Duopol; Nichtkooperatives Spiel; Theorie